2023
DOI: 10.3389/fnagi.2023.1089005
|View full text |Cite
|
Sign up to set email alerts
|

Preserved blood-brain barrier and neurovascular coupling in female 5xFAD model of Alzheimer’s disease

Abstract: IntroductionDysfunction of the cerebral vasculature is considered one of the key components of Alzheimer’s disease (AD), but the mechanisms affecting individual brain vessels are poorly understood.MethodsHere, using in vivo two-photon microscopy in superficial cortical layers and ex vivo imaging across brain regions, we characterized blood–brain barrier (BBB) function and neurovascular coupling (NVC) at the level of individual brain vessels in adult female 5xFAD mice, an aggressive amyloid-β (Aβ) model of AD.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…Consequently, development of CAA accelerates cognitive decline. [49] A recent study on AD mice have demonstrated that parenchymal accumulation of Aβ do not affect the neurovascular coupling suggesting that the impairment of cerebrovascular function in brains with Aβ accumulation is from accumulations in vessel walls [50].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, development of CAA accelerates cognitive decline. [49] A recent study on AD mice have demonstrated that parenchymal accumulation of Aβ do not affect the neurovascular coupling suggesting that the impairment of cerebrovascular function in brains with Aβ accumulation is from accumulations in vessel walls [50].…”
Section: Discussionmentioning
confidence: 99%
“…Recent vessel painting studies show that male 5xFAD mice show reduced vessel density associated with the middle cerebral artery regions and increased leakage hotspots from 4 to 12 months of age, but this was not observed in the case of female 5xFAD mice [ 50 ]. Studies by Zukhov et al and Giannoni et al show varying results on barrier integrity in female 5xFAD mice below and above 9 months of age, indicating that the effect of menopause cannot be completely excluded [ 21 , 51 ]. In this regard, the use of male 5xFAD mice excludes the effect of the estrous cycle in mice between 9 and 16 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a lack of difference in blood–brain barrier integrity between 7-and-10-month-old 5xFAD and age-matched WT mice was reported [ 51 ]. Specifically, no differences existed in vesicular transport of fluorescently labeled albumin across pial vessels, penetrating arterioles, and capillaries in 5xFAD and age-matched WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gov/, 2022; Wafa et al, 2020). There has been a limited focus in research on the natural aging of pericytes and how age-related pericyte dysfunction impacts the cerebrovasculature, with conflicting reports regarding changes in pericyte density in aged experimental animals (Montagne et al, 2021;Zhukov et al, 2023). As the body ages, there is a chronic increase in pro-inflammatory markers and reactive oxygen (ROS) and nitrogen species (RNS) (Davalli et al, 2016).…”
Section: Pericyte Roles In Ischemic Risk Factorsmentioning
confidence: 99%